Glutamine: A potentially useful supplement for athletes - Antonio, J.; Street, C. (Canadian Journal of Applied Physiology, 1999)
The role of glutamine as a possible ergogenic aid has not been posited in the scientific literature. Although there is an abundance of clinical evidence supporting the need for exogenous glutamine in the maintenance of muscle protein mass and immune system function in critically ill patients, little work has been done that examines the potential utility of glutamine for athletes engaged in heavy exercise training. This brief review will describe a number of studies on the effects of glutamine supplementation on muscle protein mass, immune system function, and glucose regulation. Based on the available clinical evidence, we would speculate that glutamine has potential utility as a dietary supplement for athletes engaged in heavy exercise training.